Epigenetic Modification: A Key Tool for Secondary Metabolite Production in Microorganisms - Bind, Sudha; Bind, Sandhya; Sharma, A. K.; Chaturvedi, Preeti (Frontiers in Microbiology, 2022)
Microorganisms are stupendous source of secondary metabolites, having significant pharmaceutical and industrial importance. Genome mining has led to the detection of several cryptic metabolic pathways in the natural producer of secondary metabolites (SMs) such as actinobacteria and fungi. However, production of these bioactive compounds in considerable amount is somewhat challenging. This led to the use of epigenetics as a key mechanism to alter the expression of those genes which encode the SMs towards higher production in microorganisms. Epigenetics is defined as any heritable change without involving the changes in the underlying DNA sequences. Epigeneticmodificationsinclude1. Chromatinremodeling by histone posttranslational modifications, 2. DNA methylation and3. RNA interference. Study of epigenetic regulation of biosynthetic gene cluster gained pivotal importance in secondary metabolite production in last two decades. Biosynthetic gene cluster for SMs remain in heterochromatin state in which transcription of constitutive gene is regulated by epigenetic modification. Therefore, small molecule epigenetic modifiers which promote changes in the structure of chromatin could control the expression of silent genes and may be rationally employed for discovery of novel bioactive compounds. This review article focuses on types of epigenetic modifications and their impact on gene expression in enhancing the production of SMs in microorganisms.